2004
DOI: 10.1038/sj.ijir.3901207
|View full text |Cite
|
Sign up to set email alerts
|

Tissue expression, distribution, and regulation of PDE5

Abstract: Phosphodiesterase 5 (PDE5) has been identified in many species. The three isoforms, PDE5A1, PDE5A2, and PDE5A3, differ only in their N-terminal sequence. PDE5A1 and PDE5A2 are ubiquitous, but PDE5A3 is specific to smooth muscle. The initial three exons (A1-A3-A2) of PDE5A, located on chromosome 4q26, are alternative first exons encoding the isoform-specific sequences. The PDE5A promoter overlaps with the A1-specific exon, while the PDE5A2 promoter is located between the A3-and A2-specific exons. Both respond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 15 publications
1
64
0
4
Order By: Relevance
“…They share similar cGMP-catalytic activities but differ at their N-terminal regions (Lin et al, 2000b). They also showed similar sensitivity to inhibition by sildenafil, although the PDE5A1 isoform seems more resistant than PDE5A2 or PDE5A3 (Lin, 2004). There are no obvious functional differences in PDE5A1, PDE5A2 and PDE5A3.…”
Section: Pde5mentioning
confidence: 75%
See 1 more Smart Citation
“…They share similar cGMP-catalytic activities but differ at their N-terminal regions (Lin et al, 2000b). They also showed similar sensitivity to inhibition by sildenafil, although the PDE5A1 isoform seems more resistant than PDE5A2 or PDE5A3 (Lin, 2004). There are no obvious functional differences in PDE5A1, PDE5A2 and PDE5A3.…”
Section: Pde5mentioning
confidence: 75%
“…However, this concept was challenged by a study demonstrating an abundant expression of PDE5 in isolated canine ventricular cardiomyocytes, as assessed by immunohistochemistry (Senzaki et al, 2001), and also in murine ventricular cardiomyocytes, as shown by RT-PCR, western blot and immunohistochemical assay (Das et al, 2005). PDE5A is generally considered to be a cytosolic protein (Lin, 2004). The sub-cellular localization of PDE5A, myocyte z-bands, was not observed when cells were isolated from failing myocytes, suggesting its intracellular localization is altered in these cells (Senzaki et al, 2001).…”
Section: Pde5mentioning
confidence: 99%
“…PDE5 enzyme on human retinal tissue C Foresta et al the corpora cavernosa of the penis, but many other organs express the PDE5 enzyme such as pulmonary and coronary vasculature, sympathetic nervous system, and Purkinje neurons, [11][12][13] where its influence is less known. Minor adverse effects of PDE5 inhibitors administration such as headache, flushing, hypotension, dyspepsia, and visual disturbances may be due to this influence and inspired many studies.…”
Section: Discussionmentioning
confidence: 99%
“…3 First purified from rat lung, 4 PDE5 has also been identified in many species and a wide variety of tissues. 5,6 A great physiological protein level of PDE5 in penile organ has been found, being 10-to 100-fold more abundant in corpus cavernosum than in other nonreproductive tissues. 7 Recent studies have shown that in mononuclear cells the level of proteins involved in the NO-cGMP system was altered in patients with ED.…”
Section: Introductionmentioning
confidence: 99%